Justice Reform: Who's Got the Power - Mayba, Yevgeniy (2015)
As the US prison population continues to rise despite the significant decrease in crime rates, scholars and social activists are demanding comprehensive reforms to the penal system that disproportionately affects minorities and the poor and has become a significant burden on the taxpayers. This paper examines some of the processes that contributed to the rise of the modern day carceral state, such as the determinate sentencing reform and the proliferation of mandatory minimum sentencing. It also explores the unintended consequences of these penal developments and traces the reaction and subsequent resistance to these sentencing schemes from the judiciary, as well as other sources. Finally, this paper examines the dynamics of power between various actors in the struggle for meaningful reforms in the penal system and argues for a concerted action aimed at stimulating meaningful action from the legislature that has so far largely abstained from major efforts at reforming the criminal justice system